N-Chloronicotinamide as an Oxidimetric Titrant: Potentiometric Titrations of Some Typical Common Reductants in Aqueous Acetic Acid Medium - Ramkumar, B. (Asian Journal of Chemistry, 2010)
N-Chloronicotinamide (NCN) has been used as an oxidimetric titrant in aqueous acetic acid medium. Potentiometric titrations of some typical common reductants have been performed using N -chloronicotinamide.